CARBON BALANCES IN SELECTED AQUACULTURE PONDS OF GUMLA DISTRICT, JHARKHAND, INDIA - BHARDWAZ, KASHISH; GHOSH, T. K.; ADHIKARI, S.; SINGH, A.K.; SIN GH, VEERENDRA; BERA, PUJA DEBI; BARMAN , SUSMITA (Journal of the Inland Fisheries Society of India, 2025)
The present work of carbon balances in some aquaculture ponds in Gumla district, Jharkhand was conducted from July 2021 to November 2022 in three ponds with feeding and three ponds in non-feeding systems of fish culture. The pond sizes varied from 0.7 to 1.62ha, and the water depth of ponds varied from 1.5 to 1.8 m. The fish culture practices consisted with Labeo rohita (Rohu), Catla catla (Catla), and Cirrhinus mrigala (Mrigal). The average fish production was 3000kg ha-1 yr-1 in feeding ponds and 1520 kg ha-1 yr-1 in non-feeding ponds. The physicochemical parameters were optimal in these ponds. The inputs used in the culture systems were lime and pelleted feed in feeding ponds only. No inputs were added in the non-feeding ponds except stocking of fish seeds. The organic carbon ranged from 5 to 8 mg/ l in pond water and from 0.6 to 1.5 percent in soils in all the ponds. Carbon accumulation in the sediment increased during the culture period in three ponds, and slightly decreased in non-three ponds. The decrease accumulation mainly occurred in non-fed ponds and this carbon could be utilized for the production of plankton. In the present study, carbon accumulation was 91 to 105 % at the fish harvest time from the initial value of 95 to 98 %. In the present study, accumulation of organic carbon occurred within 1-2 % as no inputs as nutrients were added to the three ponds, and some inputs (pelleted feed, mustard oil cake, and wheat flour) were applied to the other three ponds. Thus, as these ponds under study showed almost no accumulation, and the small inputs as carbon added to the feeding ponds were also converted in the fish flesh, these six ponds for aquaculture practices could be considered as carbon neutral.